Syntheses, structures, and magnetic properties of three new MnII–[MoIII(CN)7]4− molecular magnets. Issue 34 (22nd May 2018) - Wei, Xiao-Qin; Pi, Qian; Shen, Fu-Xing; Shao, Dong; Wei, Hai-Yan; Wang, Xin-Yi
Abstract : Three cyanide-bridged 3D long-range magnetic ordering complexes were successfully synthesized and magnetically characterized. These compounds are the first [Mo III (CN)7 ] 4− -based materials containing the bidentate secondary ligands. Abstract : By reaction of K4 [Mo III (CN)7 ]·2H2 O, Mn(ClO4 )2 ·6H2 O and bidentate chelating ligands, three new cyano-bridged compounds, namely Mn2 (3-pypz)(H2 O)(CH3 CN)[Mo(CN)7 ] (1 ), Mn2 (1-pypz)(H2 O)(CH3 CN)[Mo(CN)7 ] (2 ) and Mn2 (pyim)(H2 O)(CH3 CN)[Mo(CN)7 ] (3 ) (3-pypz = 2-(1 H -pyrazol-3-yl)pyridine, 1-pypz = 2-(1 H -pyrazol-1-yl)pyridine, pyim = 2-(1 H -imidazol-2-yl)pyridine), have been synthesized and characterized structurally and magnetically. Single crystal X-ray analyses revealed that although the chelating ligands are different, compounds1 to3 are isomorphous and crystallize in the same monoclinic space group C 2/ m . Connected by the bridging cyano groups, one crystallographically unique [Mo(CN)7 ] 4− unit and three crystallographically unique Mn II ions of different coordination environments form similar three-dimensional frameworks, which have a four-nodal 3, 4, 4, 7-connecting topological net with a vertex symbol of {4 3 }{4 4 ·6 2 }2 {4 10 ·6 11 }. Magnetic measurements revealed that compounds1–3 display long-range magnetic ordering with critical temperatures of 64, 66 and 62 K, respectively. These compounds are rare examples of a small number of chelating co-ligand coordinated [Mo(CN)7 ] 4− -based magnetic materials. Specifically, the bidentate chelating ligands were successfully introduced into the heptacyanomolybdate system for the first time.